Kualitas Perairan Muara Sungsang ditinjau dari Konsentrasi Bahan Organik pada Kondisi Pasang Surut - Sembiring, Susan MR; ., Melki; Agustriani, Fitri (Maspari Journal : Marine Science Research, 2012)
ABSTRACTThe increase of organic material into the Sungsang Estuary waters continuously can lead to changes in the composition of physical, chemical and the biological properties of these waters. The purposes of this research are assessing the value of the concentration of organic matter, knowing the water quality and the environmental factors that affect the content of TOM, BOD and COD in waters of Sungsang. Water sampling took on July, 8th to 9th, 2011 in Sungsang Estuary at high and low tide, Banyuasin regency, South Sumatera, then continued the analysis of water samples at the Laboratory of Aquatic, Cultivation vocation, University of Sriwijaya and the Environment Agency Palembang on July 13th to 24th , 2011. The results showed that the average content of TOM at high tide was 7.2 mg/l and at low tide was 9.9 mg/l. BOD values ​​at high tide was 5.1 mg/l and at low tide was 4.2 mg/l. The average value of COD at high tide was 249.8 mg/l and at low tide was 295.5 mg / l. Sungsang Estuary water quality in terms of organic matter and BOD TOM within the quality standard is exceeded while the COD content of the quality standard based on the Degree of the Minister of Environment for marine biota. The relationship among salinity, pH, temperature and DO on TOM at high tide was proportional to BOD and COD, while inversely at low tide. The relationship among salinity, pH, temperature and DO and BOD of the TOM is inversely proportional to at low tide, while the COD was proporsional.Keywords: TOM, BOD, COD ABSTRAKPeningkatan bahan organik secara terus-menerus di perairan Muara Sungsang dapat mengakibatkan perubahan sifat kimia fisika perairan dan sifat biologis dari perairan tersebut. Penelitian ini bertujuan mengkaji nilai konsentrasi bahan organik, mengetahui kualitas air, serta faktor-faktor lingkungan yang mempengaruhi TOM, BOD dan COD. Pengambilan sampel dilaksanakan pada tanggal 8-9 Juli 2011 di Muara Sungsang saat pasang surut, Kabupaten Banyuasin, Sumatera Selatan, dilanjutkan analisis sampel di Laboratorium Program Studi Budi Daya Perairan Universitas Sriwijaya dan Badan Lingkungan Hidup Palembang pada tanggal 13-24 Juli 2011. Hasil penelitian menunjukkan bahwa kandungan rata-rata TOM saat pasang 7,2 mg/l dan surut 9,9 mg/l. Nilai BOD saat pasang 5,1 mg/l dan surut 4,2 mg/l. Nilai rata-rata COD saat pasang 249,8 mg/l dan surut 295,5 mg/l. Kualitas perairan Muara Sungsang ditinjau dari bahan organik TOM dan BOD masih berada dalam batas baku mutu sedangkan kandungan COD sudah melampaui baku mutu berdasarkan Keputusan Menteri Negara Lingkungan Hidup untuk biota laut. Hubungan antara salinitas, pH, suhu dan DO terhadap TOM saat pasang adalah berbanding lurus sedangkan untuk BOD dan COD berbanding terbalik. Hubungan antara salinitas, pH, suhu dan DO terhadap TOM dan BOD saat surut adalah berbanding terbalik, sedangkan utnuk COD berbanding lurus.Kata kunci: TOM, BOD, COD